The place of grammar instruction in the 21st century: Exploring global perspectives of English teachers towards the role of teaching grammar in EFL/ESL classrooms - Al-Khresheh, Mohammad H.; Orak, Suheyla Demirkol (Sciedu Press, 2021)
This study explores the perspectives held by English teachers around the world regarding the role of teaching grammar in EFL/ESL classrooms and whether the divergence in these perspectives is influenced by variables such as gender, country, seniority, or educational background of the participants. To accomplish these objectives, a comprehensive questionnaire survey from literature comprising 46 items was carried out on a group of 304 participants from 22 countries who were voluntarily involved in this study using the snowball sampling method. Descriptive statistical methods were deployed for accurate data analysis. The findings revealed that the participants had a positive and constructive attitude regarding the importance of grammar instruction and were in unanimous agreement that good grammatical skills enabled the faster acquisition of proficiency in the target language. The participants agreed that grammatical mistakes? immediate correction was detrimental students? self-confidence levels and considered unnecessary interruption. These views highly influenced teaching methods and classroom practices. An overwhelming majority preferred an inductive and explicit approach to grammar teaching. It was concluded that while statistical differences in age, gender, and educational background did not influence the participants? perspectives, seniority and country of origin played a vital role in these beliefs. After due consideration of these findings, a comprehensive discussion of the pedagogical implications and recommendations has been presented in this study. © World Journal of English Language.
Keywords: EFL/ESL teachers; English; Grammar; Perceptions; Teaching methods